Integrated solid electrolyte composite positive electrode, preparation method thereof and prepared high-specific-energy solid-state battery
By using integrated solid electrolyte composite positive electrode and in-situ polymerized gel electrolyte in high-specific energy lithium batteries, the problems of deterioration of the positive electrode material structure and side reactions in the electrode/electrolyte interface are solved, and the high cycle stability and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202411732563.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
AI Technical Summary
The existing high-specific energy lithium batteries have problems in the deterioration of the structure of the positive electrode material and the side reactions of the electrode/electrolyte interface, resulting in poor cycle stability and safety risks.
The preparation method of integrated solid electrolyte composite positive electrode is adopted. By mixing high-lithium storage positive electrode materials, inorganic solid electrolyte, conductive agent, binder and diluent, high-speed homogenization and dispersing, wet-coated on the surface of aluminum foil, drying, and then spraying the inorganic solid electrolyte on the solid electrolyte composite positive electrode to form an integrated solid electrolyte composite positive electrode, and matching it with the in situ polymer gel electrolyte.
The structural deterioration of the positive electrode material is reduced, the side reactions of the electrode/electrolyte interface are suppressed, the interface compatibility between the positive electrode and the solid electrolyte is improved, and the cycle stability and safety performance of the battery are significantly improved.
Smart Images

Figure CN119764352A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of chemical power sources, and in particular relates to an integrated solid electrolyte composite positive electrode and a preparation method thereof and a high specific energy solid-state battery prepared therefrom. Background Art
[0002] With the continuous expansion of the new energy field, the demand for lithium battery products with higher energy density is becoming more urgent. However, from the perspective of technical potential, the energy density of liquid lithium-ion batteries based on traditional technical routes is about to hit the ceiling (300Wh / kg), and the energy density improvement has encountered a bottleneck. The use of lithium metal to replace the intercalation negative electrode in lithium-ion batteries can greatly improve the energy density of energy storage batteries, and even obtain a battery system with a specific energy of more than 700Wh / kg, which expands the application direction of secondary batteries. At the same time, there are also some problems with high-energy-density metal lithium batteries in practical applications. The negative electrode metal lithium is relatively active and is prone to side reactions with the electrolyte; the cycle performance is poor, and the uneven deposition of lithium ions on the surface of metal lithium is prone to form a large number of lithium dendrites, resulting in reduced safety. At the same time, the active metal element content of high-lithium storage positive electrode materials is extremely high, so the material is highly active and easily reacts with the electrolyte, inducing the material to undergo irreversible lattice oxygen release, accelerating the internal structural phase change of the material. The release of lattice oxygen ions will cause a series of side reactions with the electrolyte, which can further accelerate the instability of the material and the battery failure process.
[0003] Solid-state batteries have low risk of explosion and high energy density, and the market is paying close attention to their potential to become the next generation of lithium battery technology. All-solid-state electrolytes do not contain organic solvents. Inorganic oxides and organic polymer solid electrolyte materials have low conductivity, slow reaction kinetics, and poor rate performance. There are still major technical difficulties in the effective contact of the microscopic interface between solid active substances and solid electrolytes, interfacial electrochemical stability, and interfacial stress regulation. Therefore, a "quasi" solid electrolyte with properties between liquid electrolytes and all-solid-state electrolytes - gel electrolytes - has become an object of increasing attention. The state of gel polymer electrolytes (GPEs) is between that of liquid electrolytes and solid electrolytes. They can be used not only as electrolytes, but also as separators to improve the interfacial resistance of solid electrolytes and to inhibit the growth of lithium dendrites to a certain extent.
[0004] For the design of high-energy-density batteries, the compatibility of high-lithium storage cathode materials and electrolytes must be considered. Through the compounding of inorganic solid electrolyte composite cathodes and in-situ polymerized gel electrolytes, the effective microscopic interface contact and interfacial electrochemical stability between solid active materials and electrolytes can be effectively solved, and the cathode capacity can be fully and stably exerted, thereby improving the safety and high-temperature performance of the battery. Based on the composite application of inorganic solid electrolyte composite cathodes and in-situ polymerized gel electrolytes, matching lithium metal / lithium alloys through reasonable battery design can obtain a high-safety and high-energy-density battery system. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-energy-density solid-state battery using an integrated solid-state electrolyte composite positive electrode and a preparation method thereof, which can reduce the structural deterioration of the positive electrode material, inhibit the electrode / electrolyte interface side reactions, and improve the interface compatibility between the positive electrode and the solid electrolyte, thereby achieving performance improvement of the high-energy-density lithium battery.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing an integrated solid electrolyte composite positive electrode, comprising the following steps:
[0007] (1) mixing a high-lithium storage positive electrode material, an inorganic solid electrolyte, a conductive agent, a binder, and a diluent, and then uniformly dispersing the mixture through high-speed homogenization, wet-coating the mixture on the surface of an aluminum foil, and drying the mixture to prepare a solid electrolyte composite positive electrode;
[0008] (2) spraying / coating a layer of inorganic solid electrolyte on the solid electrolyte composite positive electrode to obtain an integrated solid electrolyte composite positive electrode.
[0009] The inorganic solid electrolyte is one or a combination of LATP, LLZO, LLZTO, LAGP and LGPS.
[0010] In step (1), the high lithium storage positive electrode material is layered LiCoO2, LiNiO2 and LiNi x Co 1-x O2, ternary LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.83 Co 0.11 Mn 0.06 O2、LiNi 0.85 Co 0.09 Mn 0.06 O2、LiNi 0.88 Co 0.09 Mn 0.03 O2、LiNi0.9 Co 0.05 Mn 0.05 O2、LiNi 0.92 Co 0.04 Mn 0.04 O2、LiNi 0.85 Co 0.1 Al 0.05 O2, and LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5 O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnM) 1-x ]O2 wherein M=Ni, Co, Fe; the conductive agent is one or two of conductive carbon black, conductive graphite, carbon fiber (VGCF), and carbon nanotube (CNT); the binder is polyvinylidene fluoride-hexafluoropropylene; the diluent is N-methylpyrrolidone (NMP), and the single-surface surface density of the positive electrode layer of the prepared solid electrolyte composite positive electrode is 18-30 mg / cm 2 .
[0011] The integrated solid electrolyte composite positive electrode is prepared by the above preparation method.
[0012] A method for preparing a high-energy-density solid-state battery, using the above-mentioned integrated solid-state electrolyte composite positive electrode, lithium negative electrode, and ceramic coating separator, preparing a high-energy-density soft-package lithium metal battery cell by Z-shaped lamination, and injecting an in-situ polymerized gel electrolyte into the battery cell to obtain a high-energy-density solid-state battery.
[0013] The in-situ polymerized gel electrolyte is prepared by adding one or two ester monomers to a liquid high-concentration salt electrolyte and initiating polymerization with a thermal initiator. The polymer is an ester polymer including one or more C=C double bonds.
[0014] The liquid high-concentration salt electrolyte comprises a lithium salt, a solvent and an additive, wherein the lithium salt is one or more of lithium bis(trifluoromethylsulfonate)imide, lithium bis(fluorosulfonyl)imide and lithium perchlorate; the solvent is one or more of ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,2-di(cyanoethoxy)ethane, 18-crown ether-6, diphenyl ether, 1,2-dimethoxypropane (DMP) and dimethoxymethane (DMM) which have strong solubility for the lithium salt and can form a stable chelate; the lithium salt concentration is 2.5 mol / L-6 mol / L; the ester monomer It is a combination of one or more of pentaerythritol tetraacrylate (PETEA), butyl acrylate (BA), allyl acetoacetate (AOA), 2-methylenepentanedionitrile (2MEA), hydroxyethyl acrylate (HEA), ethyl cyanoacrylate (ECA), and hydroxypropyl methacrylate (HPMA); the initiator is an azo or peroxide initiator, the azo initiator is azobisisobutyronitrile (AIBN) or 1-((cyano-1-methylethyl)azo)formamide (CMAB), the peroxide initiator is didodecanoyl peroxide (LPO) or benzamide peroxide (BPO), and the thermal initiation polymerization temperature is 60-90°C.
[0015] The ceramic components in the ceramic coating diaphragm are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), lithium lanthanum zirconium oxide (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ) and the coating thickness is 0.5-2μm.
[0016] The lithium negative electrode is one of metallic lithium and lithium alloy, and has a thickness of 20 micrometers to 80 micrometers.
[0017] The high-energy-density solid-state battery prepared by the above preparation method.
[0018] The beneficial effects of the present invention are as follows: the present invention constructs an integrated solid electrolyte composite positive electrode and matches the in-situ polymerized gel electrolyte, thereby reducing the structural deterioration of the positive electrode material, inhibiting the electrode / electrolyte interface side reaction, improving the interface compatibility between the positive electrode and the solid electrolyte, and solving the problems of poor cycle stability and potential safety hazards. On this basis, a high specific energy battery is prepared, which can effectively improve the battery cycle stability and lay the foundation for the practical application of lithium metal batteries. The method is simple and easy to implement and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 0.1C discharge curves of the batteries of Example 1 and Comparative Example 1;
[0020] Figure 2The cyclic discharge capacity and coulomb efficiency curves of the batteries of Example 1 and Comparative Example 1;
[0021] Figure 3 is a graph showing acupuncture results (3 mm needle, speed 25 mm / min) of Example 1 and Comparative Example 1;
[0022] Figure 4 It is the DSC test curve of the integrated composite modified positive electrode and the ordinary positive electrode;
[0023] Figure 5 0.1C discharge curves of batteries of Example 2 and Comparative Example 2;
[0024] Figure 6 The cyclic discharge capacity and coulomb efficiency curves of the batteries of Example 3 and Comparative Example 3;
[0025] Figure 7 This is an electron microscope image of the surface-coated inorganic solid electrolyte coating;
[0026] Figure 8 0.1C discharge curves of batteries of Example 3 and Comparative Example 3;
[0027] Fig. 9 The cyclic discharge capacity and coulomb efficiency curves of the batteries of Example 3 and Comparative Example 3;
[0028] Fig.10 This is a photo of a gel polymer electrolyte. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] The method for preparing the integrated solid electrolyte composite positive electrode of the present invention comprises the following steps:
[0031] (1) mixing a high-lithium storage positive electrode material, an inorganic solid electrolyte, a conductive agent, a binder, and a diluent, and then uniformly dispersing the mixture through high-speed homogenization, wet-coating the mixture on the surface of an aluminum foil, and drying the mixture to prepare a solid electrolyte composite positive electrode;
[0032] (2) spraying / coating a layer of inorganic solid electrolyte on the solid electrolyte composite positive electrode to obtain an integrated solid electrolyte composite positive electrode.
[0033] The inorganic solid electrolyte is one or a combination of LATP, LLZO, LLZTO, LAGP and LGPS.
[0034] In step (1), the high lithium storage positive electrode material is layered LiCoO2, LiNiO2 and LiNix Co 1-x O2, ternary LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.83 Co 0.11 Mn 0.06 O2、LiNi 0.85 Co 0.09 Mn 0.06 O2、LiNi 0.88 Co 0.09 Mn 0.03 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.92 Co 0.04 Mn 0.04 O2、LiNi 0.85 Co 0.1 Al 0.05 O2, and LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5 O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnM) 1-x ]O2 wherein M=Ni, Co, Fe; the conductive agent is one or two of conductive carbon black (SuperP, Ketjen Black, etc.), conductive graphite (KS-6, SFG-6, etc.), carbon fiber (VGCF), carbon nanotube (CNT); the binder is polyvinylidene fluoride-hexafluoropropylene; the diluent is N-methylpyrrolidone (NMP), and the single-surface surface density of the positive electrode layer of the prepared solid electrolyte composite positive electrode is 18-30 mg / cm 2 .
[0035] The integrated solid electrolyte composite positive electrode is prepared by the above preparation method.
[0036] A method for preparing a high-energy-density solid-state battery, using the above-mentioned integrated solid-state electrolyte composite positive electrode, lithium negative electrode, and ceramic coating separator, preparing a high-energy-density soft-package lithium metal battery cell by Z-shaped lamination, and injecting an in-situ polymerized gel electrolyte into the battery cell to obtain a high-energy-density solid-state battery.
[0037] Inject liquid high-concentration salt electrolyte and polymer, initiator to mix to obtain electrolyte precursor mixture, then place in vacuum equipment to evacuate for preliminary infiltration, then seal the battery to obtain a preliminary infiltration battery. The battery is then left at 25°C for 24-48 hours, and then placed in a 60-90°C oven for in-situ thermal polymerization to obtain a solid-state metal lithium battery. The battery is formed, then vented and sealed, and then performance tested.
[0038] The in-situ polymerized gel electrolyte is prepared by adding one or two ester monomers to a liquid high-concentration salt electrolyte and initiating polymerization with a thermal initiator. The polymer is an ester polymer including one or more C=C double bonds.
[0039] The liquid high-concentration salt electrolyte comprises a lithium salt, a solvent and an additive, wherein the lithium salt is one or more of lithium bis(trifluoromethylsulfonate)imide, lithium bis(fluorosulfonyl)imide and lithium perchlorate; the solvent is one or more of ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,2-di(cyanoethoxy)ethane, 18-crown ether-6, diphenyl ether, 1,2-dimethoxypropane (DMP) and dimethoxymethane (DMM) which have strong solubility for the lithium salt and can form a stable chelate; the lithium salt concentration is 2.5 mol / L-6 mol / L; the ester monomer It is a combination of one or more of pentaerythritol tetraacrylate (PETEA), butyl acrylate (BA), allyl acetoacetate (AOA), 2-methylenepentanedionitrile (2MEA), hydroxyethyl acrylate (HEA), ethyl cyanoacrylate (ECA), and hydroxypropyl methacrylate (HPMA); the initiator is an azo or peroxide initiator, the azo initiator is azobisisobutyronitrile (AIBN) or 1-((cyano-1-methylethyl)azo)formamide (CMAB), the peroxide initiator is didodecanoyl peroxide (LPO) or benzamide peroxide (BPO), and the thermal initiation polymerization temperature is 60-90°C.
[0040] The ceramic components in the ceramic coating diaphragm are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), lithium lanthanum zirconium oxide (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ) and the coating thickness is 0.5-2μm.
[0041] The lithium negative electrode is one of metallic lithium and lithium alloy, and has a thickness of 20 micrometers to 80 micrometers.
[0042] The high-energy-density solid-state battery prepared by the above preparation method.
[0043] Example 1
[0044] (1) Preparation of solid electrolyte composite positive electrode
[0045] In a dry room with an ambient humidity not higher than 1.5%, the positive electrode active material is LiNi 0.95 Co 0.02 Mn 0.03 O2 ternary material. The positive electrode active material, 80 nanometers of LATP, conductive agent (Super P:CNT = 3:2, wt%) and binder 6wt% polyvinylidene fluoride-hexafluoropropylene are mixed in a mass ratio of 96:1:1.5:1.5, and then diluted with appropriate amount of NMP. After stirring evenly, the double-sided coating is uniformly applied on 10μm aluminum foil. After drying and rolling, the single-sided surface density is 25mg / cm 2 The positive electrode sheet is then cut and punched to obtain an area of 39.6cm 2 The positive electrode.
[0046] (2) Preparation of integrated solid electrolyte composite cathode
[0047] In a dry room with an ambient humidity of no more than 1.5%, the prepared solid electrolyte composite positive electrode was placed on the table of an ultrasonic spraying device, and an LATP slurry with a solid content of 5% (dispersant: NMP) was sprayed on the surface of the prepared solid electrolyte composite positive electrode using an ultrasonic spraying device. Double-sided spraying was performed, and the surface density of the single-sided sprayed LATP layer was 0.15 mg / cm 2 , an integrated solid electrolyte composite positive electrode was obtained, and the electrode piece was vacuum dried in a vacuum drying oven at 110°C for 48 hours.
[0048] (3) High energy density battery stacking
[0049] The integrated solid electrolyte composite positive electrode, 16+2+2 ceramic coating separator, and 30-micron lithium negative electrode are used to prepare a high-energy-density soft-package lithium battery cell through a Z-shaped stacking method. The number of positive electrodes is 30. After welding the pole ears and encapsulating them in an aluminum shell, a 14Ah metal lithium battery dry cell is obtained.
[0050] (4) Preparation of gel precursor solution (in situ polymerization gel electrolyte)
[0051] 0.6wt% (based on the liquid high concentration salt electrolyte) of pentaerythritol tetraacrylate (PETEA) was added to the liquid high concentration salt electrolyte (LiTFSI: DME: TTE: EP mass ratio of 22:22:54:2), stirred at 300rpm for 3h, and after dissolution, 0.5wt% of hydroxypropyl methacrylate (HPMA) was added, and stirring was continued for 2h, and then 1wt% (mass ratio, based on the total amount of polymer added) of azobisisobutyronitrile (AIBN) was added and stirred for 30min to obtain a metal lithium gel precursor solution.
[0052] (5) High specific energy cell injection and in-situ polymerization
[0053] The gel precursor solution prepared above was injected into the high specific energy battery cell with an injection volume of 1.0g / Ah, and then placed in a vacuum oven for 3 times, each time maintaining the pressure for 10 minutes (vacuum degree -0.08MPa), and the battery was taken out and packaged with a vacuum sealer to obtain a preliminary impregnation battery. The battery was then left at 25°C for 24 hours, and then the soft-pack battery was cured in an 80-degree oven for 60 minutes, and finally a solid-state metal lithium battery was obtained.
[0054] The solid-state metal lithium battery finally obtained has a specific energy of 756Wh / kg at 0.1C, a cycle life of 52 times (coulomb efficiency is less than 98% for two consecutive weeks), a capacity retention rate of 101.7%, and passed the needle puncture test.
[0055] Example 2
[0056] (1) Preparation of solid electrolyte composite positive electrode
[0057] In a dry room with an ambient humidity not higher than 1.5%, the positive electrode active material is LiNi 0.88 Co 0.09 Mn 0.03 O2 ternary material. The positive electrode active material, 100 nanometers of LLZTO, conductive agent (Super P:CNT = 3:2, wt%) and binder 6wt% polyvinylidene fluoride-hexafluoropropylene are mixed in a mass ratio of 96.5:0.5:1.5:1.5, and then diluted with appropriate amount of NMP. After stirring evenly, the double-sided coating is uniformly applied on 10μm aluminum foil. After drying and rolling, the single-sided surface density is 20mg / cm 2 The positive electrode sheet is then cut and punched to obtain an area of 137cm 2 The positive electrode.
[0058] (2) Preparation of integrated solid electrolyte composite cathode
[0059] Step (2) refers to step (2) of Example 1.
[0060] The differences are:
[0061] The ultrasonic spraying slurry is LLZTO slurry with a solid content of 5% (the dispersant is ethanol), and the surface density of the single-sided sprayed LLZTO layer is 0.3 mg / cm 2 .
[0062] (3) High energy density battery stacking
[0063] Step (3) refers to step (3) of Example 1.
[0064] The differences are:
[0065] The negative electrode is a 20-micron lithium-magnesium alloy, and an 11Ah metal lithium battery dry cell is obtained.
[0066] (4) Preparation of gel precursor solution (in situ polymerization gel electrolyte)
[0067] 0.7wt% (based on the liquid high concentration salt electrolyte) of hydroxyethyl acrylate (HEA) was added to the liquid high concentration salt electrolyte (LiFSI: DME: TTE: TPP mass ratio of 20:20:58:2), stirred at 300rpm for 3h, and after dissolution, 0.5wt% of hydroxypropyl methacrylate (HPMA) was added, and stirring was continued for 2h. Then, 1wt% (mass ratio, based on the total amount of polymer added) of dibenzamide peroxide (BPO) was added and stirred for 30min to obtain a metal lithium gel precursor solution.
[0068] (5) High specific energy cell injection and in-situ polymerization
[0069] Step (5) refers to step (5) of Example 1.
[0070] The differences are:
[0071] The injection volume is 1.8g / Ah. The soft pack battery is cured in an oven at 70 degrees, and the heating time is 40 minutes.
[0072] The solid-state metal lithium battery finally obtained has a 1C specific energy of 469Wh / kg, a cycle life of 262 times, a capacity retention rate of 80.2%, and passed the needle puncture test.
[0073] Example 3
[0074] (1) Preparation of solid electrolyte composite positive electrode
[0075] In a dry room with an ambient humidity of no more than 1.5%, the positive electrode active material is a lithium-rich manganese-based material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The positive electrode active material, 80 nanometers of LATP, conductive agent (Super P:CNT=3:2, wt%) and binder 6wt% polyvinylidene fluoride-hexafluoropropylene were mixed in a mass ratio of 96.5:0.5:1.5:1.5, and diluted with appropriate amount of NMP. After stirring evenly, the mixture was evenly coated on both sides: 10μm aluminum foil, and after drying and rolling, a single-side surface density of 20mg / cm 2 The positive electrode sheet is then cut and punched to obtain an area of 39.6cm 2 The positive electrode.
[0076] (2) Preparation of integrated solid electrolyte composite cathode
[0077] Step (2) refers to step (2) of Example 1.
[0078] The differences are:
[0079] The surface density of the single-sided sprayed LATP layer is 0.3 mg / cm 2 .
[0080] (3) High energy density battery stacking
[0081] Step (3) refers to step (3) of Example 1.
[0082] The differences are:
[0083] The negative electrode is 50 microns of lithium, and an 11Ah metal lithium battery dry cell is obtained.
[0084] (4) Preparation of gel precursor solution (in situ polymerization gel electrolyte)
[0085] 0.5 wt% (based on the liquid high concentration salt electrolyte) of 2-methyleneglutaronitrile (2MEA) was added to the liquid high concentration salt electrolyte (LiFSI: DME: TTE: PSTPP mass ratio is 20:20:57:3), stirred at 300 rpm for 3 h, and after dissolution, 0.5 wt% hydroxypropyl methacrylate (HPMA) was added, and stirring was continued for 2 h. Then, 1 wt% (mass ratio, based on the total amount of polymer added) of didodecanoyl peroxide (LPO) was added and stirred for 30 min to obtain a metal lithium gel precursor solution.
[0086] (5) High specific energy cell injection and in-situ polymerization
[0087] Step (5) refers to step (5) of Example 1.
[0088] The differences are:
[0089] The injection volume is 2g / Ah. The soft pack battery is cured in an oven at 70 degrees, and the heating time is 60min.
[0090] The solid-state metal lithium battery finally obtained has a specific energy of 550Wh / kg at 0.1C, a cycle life of 12 times, and a capacity retention rate of 89.6%. It passed the needle puncture test.
[0091] Comparative Example 1
[0092] (1) Preparation of positive electrode
[0093] Step (1) of Reference Example 1
[0094] Difference: The cathode component does not contain 80 nanometers of LATP. LiNi 0.95 Co 0.02 Mn0.03 O2, a conductive agent (Super P:CNT=3:2, wt%) and a binder 6wt% polyvinylidene fluoride-hexafluoropropylene were mixed in a mass ratio of 97:1.5:1.5.
[0095] (2) High energy density battery stacking
[0096] Step (3) of Reference Example 1
[0097] (3) Preparation of gel precursor solution
[0098] Step (4) of Reference Example 1
[0099] (4) High specific energy cell injection and in-situ polymerization
[0100] Step (5) of Reference Example 1
[0101] Finally, a battery of comparative example 1 was obtained and compared with the battery of example 1.
[0102] Comparative Example 2
[0103] (1) Preparation of solid electrolyte composite positive electrode
[0104] Step (1) of Reference Example 2
[0105] (2) High energy density battery stacking
[0106] Step (3) of Reference Example 2
[0107] (3) Preparation of gel precursor solution
[0108] Step (4) of Reference Example 2
[0109] (4) High specific energy cell injection and in-situ polymerization
[0110] Step (5) of Reference Example 2
[0111] Finally, a battery of comparative example 2 was obtained and compared with the battery of example 2.
[0112] Comparative Example 3
[0113] (1) Preparation of solid electrolyte composite positive electrode
[0114] Step (1) of Reference Example 3
[0115] (2) Preparation of integrated solid electrolyte composite cathode
[0116] Step (2) of Reference Example 3
[0117] (3) High energy density battery stacking
[0118] Step (3) of Reference Example 3
[0119] (4) Preparation of high concentration salt electrolyte
[0120] Compared with step (4) of Example 3, the liquid high-concentration salt electrolyte is maintained at (LiFSI: DME: TTE: PSTPP mass ratio is 20:20:57:3), but no polymerization monomer or initiator is added.
[0121] (5) High specific energy cell injection
[0122] Compare with step (5) of Example 3. However, the injected electrolyte is the liquid high-concentration salt electrolyte prepared in step (4) of this example, and no thermal polymerization reaction is performed.
[0123] Finally, a battery of comparative example 3 was obtained and compared with the battery of example 3.
[0124] Table 1 is a comparison of the battery electrical performance and safety performance of the solid electrolyte composite positive electrode in Example 1 of the present invention and the ordinary positive electrode in Comparative Example 1. The results show that the battery specific energy of the solid electrolyte composite positive electrode is equivalent to that of the ordinary positive electrode, both exceeding 750Wh / kg ( Figure 1 ), charge and discharge cycle at 0.2C rate (voltage range 3V~4.1V), cycle life increased from 42 times to 52 times (when the coulomb efficiency is less than 98% for two consecutive cycles, the life is considered to be over) ( Figure 2 ), indicating that the positive electrode cycle stability has been improved, especially through the 3mm needle puncture test ( Figure 3 ), the safety performance is significantly improved. Because the addition of nano solid electrolyte can inhibit the release of active oxygen in the fully charged high nickel ternary material, the heat released by the thermal decomposition of the positive electrode material is significantly reduced ( Figure 4 , the red curve is the integrated composite positive electrode, and the black curve is the ordinary positive electrode), which effectively improves the intrinsic thermal stability of the positive electrode.
[0125] Table 1
[0126]
[0127] Table 2 is a comparison of the battery electrical performance and safety performance of the integrated solid electrolyte composite positive electrode in Example 2 of the present invention and the solid electrolyte composite positive electrode in Comparative Example 2. The results show that the specific energy test discharge curves of the integrated solid electrolyte composite positive electrode and the solid electrolyte composite positive electrode are almost the same ( Figure 5 ) exceeded 460Wh / kg, and the cycle life (discharge capacity is not less than 80% of the initial capacity) increased from 230 times to 262 times ( Figure 6 ), indicating that the positive electrode cycle stability has been improved, especially through the 3mm needle puncture test, the safety performance has been significantly improved. Because the nano solid electrolyte modifies the surface of the composite positive electrode ( Figure 7 ), inhibiting the structural deterioration of the positive electrode material, inhibiting the side reaction at the electrode / electrolyte interface, improving the interfacial compatibility between the positive electrode and the solid electrolyte, and effectively improving the cycle performance and safety performance of the battery.
[0128] Table 2
[0129]
[0130] Table 3 is a comparison of the battery electrical properties and safety performance of the gel electrolyte in Example 3 of the present invention and the high-concentration salt electrolyte in Comparative Example 3. Compared with the liquid high-concentration salt electrolyte, the application of the gel electrolyte maintains the electrical properties basically unchanged ( Figure 8 , Fig. 9 ), the battery passed the 3mm needle puncture test, and its safety was significantly improved. This shows that due to the significant reduction in the liquid content in the gel electrolyte ( Fig.10 ), which has a significant impact on improving safety performance.
[0131] Table 3
[0132]
[0133] The positive electrode and electrolyte of lithium metal batteries are the basis for obtaining high specific energy, stable cycle and improved safety. By doping the high lithium storage positive electrode material with inorganic solid electrolyte and modifying the inorganic solid electrolyte on the electrode surface, an integrated composite solid electrolyte positive electrode is obtained. When introduced into the battery system to obtain high specific energy, the polymer gel electrolyte has a significant impact on the improvement of the safety of high specific energy batteries due to the greatly reduced organic liquid content. The matching use of the integrated composite solid electrolyte positive electrode and the polymer gel electrolyte can realize the construction and performance improvement of high specific energy lithium batteries.
[0134] The present invention obtains an integrated composite electrode with high electrical performance and safety performance by mixing a solid electrolyte with a positive electrode and modifying the surface, and constructs a high specific energy lithium metal battery with an in-situ gel polymer electrolyte. This method is simple and easy to implement, suitable for large-scale preparation, and provides a practical way for industrial production. It can be applied to the field of drones that have higher requirements for the endurance of energy storage batteries.
[0135] The embodiments described above are only used to illustrate the technical ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. The patent scope of the present invention cannot be limited only by this embodiment, that is, any equivalent changes or modifications made to the spirit disclosed by the present invention still fall within the patent scope of the present invention.
Claims
1. A method for preparing an integrated solid electrolyte composite positive electrode, characterized in that: The following steps are involved: (1) mixing a high-lithium storage positive electrode material, an inorganic solid electrolyte, a conductive agent, a binder, and a diluent, and then uniformly dispersing the mixture through high-speed homogenization, wet-coating the mixture on the surface of an aluminum foil, and drying the mixture to prepare a solid electrolyte composite positive electrode; (2) spraying / coating a layer of inorganic solid electrolyte on the solid electrolyte composite positive electrode to obtain an integrated solid electrolyte composite positive electrode.
2. The method for preparing the integrated solid electrolyte composite positive electrode according to claim 1, characterized in that: The inorganic solid electrolyte is one or a combination of LATP, LLZO, LLZTO, LAGP and LGPS.
3. The method for preparing the integrated solid electrolyte composite positive electrode according to claim 1, characterized in that: In step (1), the high lithium storage positive electrode material is layered LiCoO2, LiNiO2 and LiNi x Co 1-x O2, ternary LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.83 Co 0.11 Mn 0.06 O2、LiNi 0.85 Co 0.09 Mn 0.06 O2、LiNi 0.88 Co 0.09 Mn 0.03 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.92 Co 0.04 Mn 0.04 O2、LiNi 0.85 Co 0.1 Al 0.05 O2, and LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5 O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnM) 1-x ]O2 wherein M=Ni, Co, Fe; the conductive agent is one or two of conductive carbon black, conductive graphite, carbon fiber (VGCF), and carbon nanotube (CNT); the binder is polyvinylidene fluoride-hexafluoropropylene; the diluent is N-methylpyrrolidone (NMP), and the single-surface surface density of the positive electrode layer of the prepared solid electrolyte composite positive electrode is 18-30 mg / cm 2 .
4. An integrated solid electrolyte composite positive electrode prepared by the preparation method according to any one of claims 1 to 3.
5. A method for preparing a high specific energy solid-state battery, characterized in that: The integrated solid electrolyte composite positive electrode, lithium negative electrode and ceramic coating diaphragm described in claim 4 are used to prepare a high-energy-density soft-package lithium metal battery cell by Z-shaped lamination, and the battery cell is injected with in-situ polymerized gel electrolyte to prepare a high-energy-density solid-state battery.
6. The method for preparing a high specific energy solid-state battery according to claim 5, characterized in that: The in-situ polymerized gel electrolyte is prepared by adding one or two ester monomers to a liquid high-concentration salt electrolyte and initiating polymerization with a thermal initiator. The polymer is an ester polymer including one or more C=C double bonds.
7. The method for preparing a high specific energy solid-state battery according to claim 6, characterized in that: The liquid high-concentration salt electrolyte comprises a lithium salt, a solvent and an additive, wherein the lithium salt is one or more of lithium bis(trifluoromethylsulfonate)imide, lithium bis(fluorosulfonyl)imide and lithium perchlorate; the solvent is one or more of ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,2-di(cyanoethoxy)ethane, 18-crown ether-6, diphenyl ether, 1,2-dimethoxypropane (DMP) and dimethoxymethane (DMM) which have strong solubility for the lithium salt and can form a stable chelate; the lithium salt concentration is 2.5 mol / L-6 mol / L; the ester monomer It is a combination of one or more of pentaerythritol tetraacrylate (PETEA), butyl acrylate (BA), allyl acetoacetate (AOA), 2-methylenepentanedionitrile (2MEA), hydroxyethyl acrylate (HEA), ethyl cyanoacrylate (ECA), and hydroxypropyl methacrylate (HPMA); the initiator is an azo or peroxide initiator, the azo initiator is azobisisobutyronitrile (AIBN) or 1-((cyano-1-methylethyl)azo)formamide (CMAB), the peroxide initiator is didodecanoyl peroxide (LPO) or benzamide peroxide (BPO), and the thermal initiation polymerization temperature is 60-90°C.
8. The method for preparing a high specific energy solid-state battery according to claim 5, characterized in that: The ceramic components in the ceramic coating diaphragm are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), lithium lanthanum zirconium oxide (Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ) and the coating thickness is 0.5-2μm.
9. According to the method for preparing a high-energy-density solid-state battery in claim 5, the lithium negative electrode is one of metallic lithium and lithium alloy, and has a thickness of 20 microns to 80 microns.
10. A high-energy-density solid-state battery prepared by the preparation method according to any one of claims 5 to 9.
Citation Information
Patent Citations
High voltage lithium battery cell and preparation method therefor, and lithium ion battery
CN105470576A
Solid-state lithium battery and production method thereof
CN113054241A
Solid Polymer Electrolyte Battery And Method For Manufacturing Positive Electrode Sheet Used Therein
US20080020283A1
Cited By
Preparation method of in-situ solid-state battery structure
CN120341225A